1988
DOI: 10.1016/s0022-5347(17)42720-0
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Marker Chromosomes in Superficial Transitional Cell Carcinoma of the Bladder: 50 Patients Followed up to 17 Years

Abstract: Several tenets based on cytogenetic analysis have been developed for noninvasive and submucosal invasive carcinoma of the bladder. In noninvasive carcinoma absence of marker chromosomes (abnormal morphological forms) forecasts a 90 per cent post-resection cure. In submucosal invasive carcinoma marker chromosomes are valuable prognostic aids. Original marker chromosomes are neither replaced nor supplemented by a different marker in recurrences. To test these tenets the cytogenetics of 50 selected carcinomas of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1990
1990
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…More sophisticated techniques such as flow cytometry and tumour-antigen expression have been studied recently but are not yet part of daily clinical practice, in spite of their value, for lack of necessary equipment [15][16][17][18]. More sophisticated techniques such as flow cytometry and tumour-antigen expression have been studied recently but are not yet part of daily clinical practice, in spite of their value, for lack of necessary equipment [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…More sophisticated techniques such as flow cytometry and tumour-antigen expression have been studied recently but are not yet part of daily clinical practice, in spite of their value, for lack of necessary equipment [15][16][17][18]. More sophisticated techniques such as flow cytometry and tumour-antigen expression have been studied recently but are not yet part of daily clinical practice, in spite of their value, for lack of necessary equipment [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…The 25 T 1 tumors included in this study were all marker-positive and 80°7o of them recurred; 12 cancer deaths occurred within a follow-up period of 3 months to 6 years. Despite the appearance that the absence of marker chromosomes was predictive of long-term remission for patients with grade 1 or 2 Ta tumors, a recent analysis of 50 selected consecu.tive tumors of similar stage and grade that were followed for up to 17 years failed to substantiate this, since 50% of the patients with Ta-marker-negative tumors recurred within an average follow-up period of 9 years [18]. Subsequent death due to cancer, however, was limited to patients with marker-positive tumors (Ta, 38%; T1, 62%).…”
Section: Marker Chromosomesmentioning
confidence: 99%
“…Chromosomal abnormalities, including increased or decreased number of chromosomes (hyperdiploidy and aneuploidy), marker chromosomes, and the chromosomes of abnormal size or configuration, have also been shown to correlate with an increased risk of tumor recurrence and cancer progression [Sandberg et al, 1986;Falor and Ward-Skinner, 1988]. Molecular genetic studies on bladder cancer have demonstrated deletion of several chromosomal arms, including 3p, 6q, 9q, 11p, 17p, and 18q [Sandberg and Berger, 1994].…”
Section: Genetic Alterationsmentioning
confidence: 99%